In situ generated nanozyme-initiated cascade reaction for amplified surface plasmon resonance sensing. Issue 33 (24th March 2020) - Wang, Xin; Lv, Wenxin; Wu, Jiahui; Li, Haiyin; Li, Feng
Abstract : A novel nanozyme-amplified surface plasmon resonance (SPR) sensor was successfully developed based on target-induced in situ generation of AuNPs and a AuNP-guided cascade amplification reaction, with Hg 2+ as the target analyte. Abstract : A novel nanozyme-based surface plasmon resonance (SPR) sensor was successfully developed based on the target-induced in situ generation of AuNPs and a AuNP-guided cascade reaction, with Hg 2+ as the target analyte.